DAMPAK PERUBAHAN PRODUKTIVITAS SEKTORAL BERBASIS INVESTASI TERHADAP DISPARITAS EKONOMI ANTAR WILAYAH DAN KONDISI MAKROEKONOMI DI INDONESIA - Yeti Lis Purnamadewi; Mangara Tambunan; Rina Oktaviani; Arief Daryanto (School of Business, Bogor Agricultural University (SB-IPB), 2010)
The objective of this study is to examine the impact of sectoral investment on regional disparity, and macroeconomic performances in Indonesia. Investment have an important role in increasing productivity in order to encourage economic growth and equity. Investment allocation in Indonesia is biased to industry sector and to Java island. Eventhough structural change in Indonesian economy have been excisting, this structural change is associated with the shift from a predominantly agricultural economy to one dominated by the industry and service sectors, but most of the regional economy are still dominated by agriculture sector and this sector has highest contribution on employment absorption. Model of CGE multiregional is a comfortable method to analyse that aims of the study. The main finding was that the priority of investment allocation into the agriculture, agro-industry and infrastructure sectors or implementation of the ADLI strategy supported by infrastructure construction results the best impact on growth and on decreasing regional disparity. But, the ADLI strategy supported by infrastructure construction has a weakly impact on increasing the investment expenditure and export.